2014
DOI: 10.1002/eji.201344381
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of human antigen‐specific regulatory T cells with high suppressive function

Abstract: Adoptive transfer of regulatory T (Treg) cells could be an alternative to chronic immunosuppression for prevention of allogeneic graft rejection. While polyspecific Treg cells can prevent immune responses under lymphopenic conditions, Ag-specific Treg cells are needed to treat autoimmunity and graft rejection. Yet, reliable markers for Ag-specific Treg cells are missing. We report that latency-associated peptide (LAP) and glycoprotein A repetitions predominant (GARP) can identify human Ag-specific Treg cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 41 publications
4
39
0
Order By: Relevance
“…The expression of IL-10 transcript, together with the relative increase in Lrrc32 and Foxp3 transcripts in the CD154 − population compared to the CD154 + population (Figure 3D and 4C), was consistent with previous reports showing that regulatory T cells lack pre-formed CD154 and that induced regulatory T cells are unlikely to be included in the CD154 + population [4345]. …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The expression of IL-10 transcript, together with the relative increase in Lrrc32 and Foxp3 transcripts in the CD154 − population compared to the CD154 + population (Figure 3D and 4C), was consistent with previous reports showing that regulatory T cells lack pre-formed CD154 and that induced regulatory T cells are unlikely to be included in the CD154 + population [4345]. …”
Section: Resultssupporting
confidence: 91%
“…Expression microarray analysis performed on mycobacteria-specific CD4 + T cells further supported the validity of using CD154 expression as a surrogate marker for antigen-specificity. In addition, microarray analysis revealed that while multiple functional T helper subsets were present in the CD154 + population, antigen-specific regulatory T cells were likely to be excluded, consistent with previous reports in the literature [4345]. …”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, it has been demonstrated that Hsp90-mediated Hsp70 induction is necessary for promoting T reg survival and suppressive function. Strikingly, CD4 + CD25 + LAP + iT regs demonstrated high suppressive and antigen-specific capacity, substantiating a recent report describing LAP + expression on CD4 T cells as a reliable marker for the identification of antigen-specific T regs [28]. Furthermore, Mahalingam et al [67] demonstrated that isolated CD4 + CD25 + LAP + showed higher suppressive activity than CD4 + CD25 + LAP 2 , underscoring the use of LAP expression for identification of a potent, suppressive subgroup of T regs .…”
Section: Discussionsupporting
confidence: 80%
“…In recent years, GARP is discovered to express highly on the surface of activated human Tregs in vitro [36]. Freshly isolated human Tregs and Tregs clones express a low level of surface GARP.…”
Section: Treg Markersmentioning
confidence: 99%